New species of Tyrannoraptor Mendes, Oliveira, Chamorro-Rengifo & Rafael, 2018 (Orthoptera: Tettigoniidae: Meconematinae: Phlugidini) with asymmetrical jaws from the Brazilian Amazon Rainforest - Mendes, Diego Matheus De Mello; Sobral, Rafael; Neto, Alberto Moreira Da Silva (Zootaxa, 2023)
Tyrannoraptor Mendes, Oliveira, Chamorro-Rengifo & Rafael, 2018 (Tettigoniidae: Meconematinae: Phlugidini) is currently a monotypic genus. The type-species Tyrannoraptor arboreus (Nickle, 2003) is recorded to Peru (Loreto) and Brazil (Amazonas). In this work, we describe the second species of the genus, Tyrannoraptor venator sp. nov., recorded to the Brazilian Amazon rainforest. The new species is described based on a male and three female specimens. A key to species of Tyrannoraptor and a distribution map of the genus are provided as well as comments on the natural history of the new species.